The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/electronics9050778
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diseases Based on the Use of Inertial Sensors: A Systematic Review

Abstract: Inertial sensors are commonly embedded in several devices, including smartphones, and other specific devices. This type of sensors may be used for different purposes, including the recognition of different diseases. Several studies are focused on the use of accelerometer signals for the automatic recognition of different diseases, and it may empower the different treatments with the use of less invasive and painful techniques for patients. This paper aims to provide a systematic review of the studies available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
0
7
0
2
Order By: Relevance
“…Hence, they can be implemented as wearable devices (e.g., smartwatches, fitness bands, and smart clothing [9,10]). Because human health problems are most often expressed as measurable behaviors [11], IMUs are more suitable for daily activity data collection than other sensors. Hence, many IMUbased HAR studies have been accomplished [3][4][5]9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they can be implemented as wearable devices (e.g., smartwatches, fitness bands, and smart clothing [9,10]). Because human health problems are most often expressed as measurable behaviors [11], IMUs are more suitable for daily activity data collection than other sensors. Hence, many IMUbased HAR studies have been accomplished [3][4][5]9].…”
Section: Introductionmentioning
confidence: 99%
“…Entropy and statistical parameters such as mean value, standard deviation and variance are other sensible metrics [ 28 , 31 ]. Several features, extracted from both the time and frequency domain and different machine learning (ML) algorithms have been employed to classify FOG and pre-FOG events [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that remote mobility measurement systems requiring the usage of a wearable sensor can have dropout rates of up to 32% after 6 months and 50% after a year [ 10 ]. Smartphones, ubiquitous, portable, user-friendly and affordable devices with one or several embedded inertial sensors, offer a promising new avenue for the analysis of the mobility performance of PD patients outside clinical environments, complementing the capacity measures obtained in-consultation and yielding rater-independent, quantitative outcomes with higher ecological validity [ 11 , 12 ]. The validity of smartphone applications for this purpose has been shown in healthy subjects and in PD patients, albeit mostly in supervised environments, requiring the device to be worn in a predetermined location and orientation, and not accounting for the heterogeneity of smartphone usage among the population [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%